2015
DOI: 10.1210/er.2015-1018
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Statement on the Diagnostic Criteria, Epidemiology, Pathophysiology, and Molecular Genetics of Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a heterogeneous and complex disorder that has both adverse reproductive and metabolic implications for affected women. However, there is generally poor understanding of its etiology. Varying expert-based diagnostic criteria utilize some combination of oligo-ovulation, hyperandrogenism, and the presence of polycystic ovaries. Criteria that require hyperandrogenism tend to identify a more severe reproductive and metabolic phenotype. The phenotype can vary by race and ethnicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
614
0
29

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 775 publications
(652 citation statements)
references
References 483 publications
(330 reference statements)
9
614
0
29
Order By: Relevance
“…Indeed, 50-80% of PCOS women are obese, whereas 44-70% are resistant to insulin (Dumesic et al 2015). Obesity has been associated with more severe PCOS symptoms, whereas treatments directed to weight loss, such as exercise and anorexic drugs, significantly improve reproductive parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, 50-80% of PCOS women are obese, whereas 44-70% are resistant to insulin (Dumesic et al 2015). Obesity has been associated with more severe PCOS symptoms, whereas treatments directed to weight loss, such as exercise and anorexic drugs, significantly improve reproductive parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous mechanisms correlating obesity and PCOS have been proposed, one of which consists in elevated insulinemia due to increased fat deposition, hypertriglyceridemia, and insulin resistance. It is important to notice that hyperinsulinemia has been proposed as a culprit for PCOS, and the concurrence of hyperinsulinemia/insulin resistance has higher prevalence in PCOS women, independent of body weight (Wu et al 2014a, Dumesic et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Recent hypothesis-free genome-wide association studies using high-density genotyping arrays that systematically investigate common variants across the genome have identified several genetic loci to be significantly associated with PCOS (Table 2). 56 These have shed light on the important role of the gonadotropin axis in the pathogenesis of PCOS, as well as several other novel pathways, including epidermal growth factor signalling. Interestingly, genetic studies have revealed a significant overlap of findings when different diagnostic criteria of PCOS have been applied, highlighting greater homogeneity than previously appreciated.…”
Section: Recent Insights From Genetic Studiesmentioning
confidence: 99%
“…Interestingly, genetic studies have revealed a significant overlap of findings when different diagnostic criteria of PCOS have been applied, highlighting greater homogeneity than previously appreciated. 16,56,57 Clinical features and co-morbidities…”
Section: Recent Insights From Genetic Studiesmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) afflicts ∼15% of women in their reproductive years (1). PCOS women exhibit high circulating levels of testosterone (T), intermittent or absent menstrual cycles, and polycystic ovaries on ultrasound, or at least two of these three diagnostic criteria (2).…”
mentioning
confidence: 99%